ANALISIS PENGARUH AKSESIBILITAS DAN INFORMASI TERHADAP MINAT WISATAWAN BERKUNJUNG KE OBJEK WISATA PUNCAK TARUKO, KOTO GADANG, KECAMATAN IV KOTO, KABUPATEN AGAM, SUMATERA BARAT - Reza Rezita; Novera Martilova (CV. Adiba Aisha Amira, 2023)
This study aims to determine whether accessibility and information affect the interest of tourists visiting the tourist attraction Puncak Taruko Koto Gadang, District IV Koto, Agam Regency, West Sumatra. The type of research used is the type of quantitative research (quantitative methods). Data collection techniques are carried out using questionnaires. The population in this study is all tourists who have visited the Taruko Peak tourist attraction by sampling using a non-probability sampling method with purposive sampling techniques with a sample of 100 respondents. Based on the results of the study, it shows that accessibility variables have a significant effect on tourist interest with a calculated t value > t table (2.742 > 1.985) and a significant value of 0.004 < 0.05 with a coefficient value of 0.075. Furthermore, information also has a significant effect on tourist interest, with a calculated t value greater than the table t (3.365 > 1.985) and a significant value of 0.001 < 0.05 with a coefficient value of 0.305. Accessibility and information have a significant effect on tourist interest in visiting Taruko Peak attractions based on the F test with f-count > f-table (6,260 > 3.10). The contribution of accessibility and information variables to tourist interest of 0.413 or 41.3% is in the medium category.